KECEMBURUAN DAN PERILAKU DATING VIOLENCE PADA MAHASISWA - Tania Hanifah Agustin; Yuarini Wahyu Pertiwi (CV. ADIBA AISHA AMIRA, 2023)
Dating is a process of introduction between two human beings to get to know each other more deeply, a man and a woman, before they decide to proceed to a more serious level such as marriage. Not infrequently, in this relationship there are conflicts and problems. One of the conflicts that occurs in dating relationships often leads to cases of violence. Unfortunately, the problem of dating violence is not yet known by the general public. The aim of this research is to determine the relationship between jealousy and dating violence behavior in college students. This research uses quantitative methods that are correlational in nature. The subjects in this research were students who met the inclusion criteria, with a total sample of 100 people taken using non-probability sampling techniques with the Convenience Sampling type. The instrument used in this research is a Likert scale to measure the behavioral variables of dating violence and jealousy. Data were analyzed using correlation tests with statistical software. The results of the correlation test carried out show a positive relationship, which can be interpreted as the higher/increasing jealousy, the higher/increasing dating violence behavior. Conversely, if the lower the jealousy, the lower the dating violence behavior will be. The advice given to students is that they are expected to be more able to control themselves in relationships and avoid violence